Spectral properties of solar wind plasma flux and magnetic field fluctuations across fast reverse interplanetary shocks - Sapunova O. V.; Borodkova N. L.; Zastenker G. N. (Solar-Terrestrial Physics)
We have analyzed spectra of fluctuations in the solar wind plasma flux and the magnetic field magnitude near the front of a fast reverse shocks, using data from the BMSW device (Bright Monitor of Solar Wind) operating on the SPEKTR-R satellite. Its time resolution made it possible to study plasma flux fluctuations up to a frequency of 16 Hz. Magnetic field data was taken mainly from the WIND satellite, for which the frequency of the fluctuations considered was up to 5.5 Hz. The slope of the spectra of the solar wind flux fluctuations on MHD scales has been shown to be close to the slope of the spectrum of magnetic field fluctuations in the disturbed region. On kinetic scales, the difference can be significant. For the region ahead of the front, the difference in the slope of the spectrum can be quite large both in the MHD and in the kinetic region. The frequency of the break of the flux spectrum ranges from 0.6 to 1.3 Hz, which corresponds to the scale of the proton inertial length. In a number of events, however, the shape of the spectrum indicates the influence of the proton gyroradius frequency, which is usually 0.05–0.15 Hz. The break in the power spectrum of magnetic field fluctuations also more often ranges from 0.7 to 1.2 Hz. In this case, the slope of the MHD part of the spectrum changes little, but in the kinetic part it increases slightly when moving to the disturbed region.